Developing Pancasila And Citizenship Education Lesson Plan Based On 2013 Curriculum In Senior High School - Kusumawati, Intan; Paiman, Paiman; Ari Bowo, Ahmad Nasir (Universitas Pendidikan Indonesia, 2021)
This study is aimed to find out the implementation, constraints and solutions that can be done in developing Pancasila Education and Citizenship (PPKn) learning at the senior high school level. This study was conducted in senior high schools in Bantul District, Special Region of Yogyakarta. This study used qualitative research method to see how Pancasila Education and Citizenship lesson plan was developed in 2013 curriculum. This research was to look at the steps taken by teachers in preparing the lesson plan of Pancasila and Citizenship Education subject and avoiding obstacles during its implementation. Data were collected using research instruments through the goegle form as well as face-to-face interviews, observations, and discussions. the lesson plan of Pancasila and citizenship education subject was used to estimate and project the activities during teaching and learning. its lesson plan was developed from the syllabus to achieve basic competence. The implementation of Pancasila and Citizenship Education learning is an effort to foster the quality of citizens so that one day they become good people who has noble Indonesian characters and personalities based on the values of Pancasila as the foundation of United Nation of the Republic of Indonesia.